Effect of pool fire scale of heavy fuel oil on the characteristics of PAH emissions. (1st January 2019) - Cheng, Li-Hsin; Yeh, Chi-Fu; Tsai, Kuang-Chung; Lee, Pei-Fang; Tseng, Tzu-Ping; Huang, Li-Jen; Yeh, Shu-Hsing; Hsu, Hui-Tsung; Lin, Ching-Ho; Lai, Chin-Hsing; Brimblecombe, Peter; Chen, Ming-Jen
Graphical abstract: Abstract: A series of pilot-scale pool test fires simulated an idealized fire accident in a storage tank containing low-sulfur No. 6 heavy fuel oil (LSFO6). This work demonstrates that the combustion characteristics of LSFO6 and shows that fire-related emission factors (EFs) of 16 USEPA PAHs during pool fires very much depend on the scale of oil pan diameter ( D ). Over the range studied ( D  = 20–60 cm), the combustion characteristics, (i) fuel mass loss rate, (ii) heat flux and (iii) ratio of CO/CO2 as time-weighted averages have positive linear relationships with D, but the combustion efficiency is a negative linear function of D . The sum of 16 PAH EFs has a negative linear function of D, while the overall vapor-particulate partitioning coefficient of 16 PAHs has a positive linear function of D . Most benzo(a)pyrene-toxic equivalents (BaPeq) for a given pool scale arise from high-molecular-weight PAHs. However, the maximum total BaPeq occurs at pool fire scale of D  = 40 cm. The scale of burning causes no significant variation in PAH source identifications in terms of the defined molecular diagnostic ratios. Further researches on large-scale pool test fires are needed to validate whether the applicability of pilot-scale studies will be acceptable to the relevant oil tank fires in industries.